ANALISIS KEMAMPUAN MENULIS TEKS DESKRIPSI PESERTA DIDIK KELAS III B SD XAVERIUS 3 PALEMBANG - Lusia Claudia Febiyanti (Jurnal PGSD Musi, 2023)
The background of this study was to determine the ability to write descriptive texts of third grade students at SD Xaverius 3 Palembang. The purpose of the study was to determine the ability to write descriptive texts of third grade students at SD Xaverius 3 Palembang. This research is entitled "Analysis of the Ability to Write a Description Text of Class III B Students at SD Xaverius 3 Palembang". This study uses a qualitative descriptive method, namely to describe and analyze people's thoughts individually. There are two methods of collecting data, namely population and samples taken from research at SD Xaverius 3 Palembang and obtained 23 students in class III B. close of 23 students are less able to write descriptive text. From the results of the research and discussion, it can be said that all third grade students are less able to write descriptive text with the theme "Objects in class".